Jennifer, Hecate, Macbeth, William McKinley, and me, Elizabeth - Konigsburg, E. L. (New York Aladdin Paperbacks, 2001)
Two fifth-grade girls, one of whom is the first black child in a middle-income suburb, play at being apprentice witches.
A Newbery Honor Book.
Keywords: Friendship -- Fiction; Witchcraft -- Fiction; African Americans -- Fiction